The nature of forensic ethics in bioanalytical science - Shogar, Ibrahim Adam Ahmed; Abdul Hamid, Shafida; Mohd Yusof, Nazri (IIUM Press, 2019)
The pragmatic nature of bioanalytical science, a sub-discipline of analytical chemistry, is increasingly becoming central to address the practical needs of human community. It seems very potential to play a major role in many fields of industrial, environmental and medical applications. It nevertheless, encompasses various forms of analytical chemistry, such as: bioanalysis for medical and clinical purposes, especially in the pharmaceutical industry; quality assurance in food industry and products; bioanalysis for environmental and ecosystem; and bioanalysis for forensic purposes. The practical part of all these sciences depends mainly on bioanalytical chemistry, which is based on techniques and technologies characterized by accuracy, preciseness and honesty. To harness potentials of the newly growing science of bioanalysis, thus, the analytical chemists need to address, not only matters of method and techniques, but also the ethical implications of bioanalysis, especially the forensic science. The ethical concerns are practically arising alongside with the bioanalytical science: techniques adopted, application methods, fraudulent cases, negligence, besides other problems that may jeopardize the integrity of bioanalytical science. This article focuses, especially, on the ethical aspects of forensic science which depends solely upon bioanalytical chemistry. Forensic science is concerned with using results of bioanalysis for legal purposes to draw evidences for conviction. Although there is a considerable work on forensic science, however, the ethical dimension of this science needs further investigation, especially with highlighting the technical part of bioanalytical chemistry, as aimed by this article. In the first part the article outlines, briefly, the basic issues of bioanalytical science; then it investigates in the second part the ethical implications of forensic science. The method adopted is theoretical, critic, and analytical in nature.